Attractiveness, Trustworthiness and Purchase Intention in Social Media Instagram: The Moderating Role of The Number of Followers - Dewi Tamara; Rudy Rafly; Arimbi Mersi (Syntax Idea, 2021)
This study examines the influence of influencers' credibility on purchase intention on Instagram. The framework in this study includes attractiveness and trustworthiness as an indicator of influencer credibility and independent variables, number of followers as moderator, and purchase intention as dependent variable. Respondents in this study were 200 Instagram users in Indonesia who had done via Instagram. The results show that attractiveness and trust have a positive effect on purchase intention. And, the number of followers moderates the relationship between attractiveness to purchase intention and trustworthiness to purchase intention. In addition, the results of this study also prove that the number of followers has a direct influence on purchase intention. This study contributes to the product endorsement literature, how an influencer can increase the purchase intention of a consumer on Instagram social media.